Impacts and management of feral cats Felis catus in Australia. (21st November 2016) - Doherty, Tim S.; Dickman, Chris R.; Johnson, Chris N.; Legge, Sarah M.; Ritchie, Euan G.; Woinarski, John C. Z.
Abstract: Feral cats are among the most damaging invasive species worldwide, and are implicated in many extinctions, especially in Australia, New Zealand and other islands. Understanding and reducing their impacts is a global conservation priority. We review knowledge about the impacts and management of feral cats in Australia, and identify priorities for research and management. In Australia, the most well understood and significant impact of feral cats is predation on threatened mammals. Other impacts include predation on other vertebrates, resource competition, and disease transmission, but knowledge of these impacts remains limited. Lethal control is the most common form of management, particularly via specifically designed poison baits. Non‐lethal techniques include the management of fire, grazing, food, and trophic cascades. Managing interactions between these processes is key to success. Given limitations on the efficacy of feral cat management, conservation of threatened mammals has required the establishment of insurance populations on predator‐free islands and in fenced mainland enclosures. Research and management priorities are to: prevent feral cats from driving threatened species to extinction; assess the efficacy of new management tools; trial options for control via ecosystem management; and increase the potential for native fauna to coexist with feral cats.